Prevalent and persistent oncogenic HPV types in a cohort of women living with HIV prior to HPV vaccination. Issue 1 (3rd June 2020) - McClymont, Elisabeth; Lee, Marette; Raboud, Janet; Coutlée, François; Walmsley, Sharon; Lipsky, Nancy; Loutfy, Mona; Trottier, Sylvie; Smaill, Fiona; Klein, Marina B.; Harris, Marianne; Cohen, Jeffrey; et al.
Abstract: Objective: To describe prevalent and persistent oncogenic human papillomavirus (HPV) types detected in women living with HIV (WLWH) in Canada, including women with cervical dyskaryosis, and to determine predictors of type‐specific HPV persistence. Methods: Women and girls living with HIV, recruited from 14 sites of HIV care across Canada, were included in a sub‐analysis of a prospective vaccine immunogenicity cohort study (two HPV DNA results, at least one cervical cytology result pre‐vaccination). Demographic and clinical data were collected alongside cervical samples for cytology and HPV DNA typing between November 25, 2008, and May 19, 2015. Results: Pre‐vaccination, HPV16 and HPV52 were the most prevalent oncogenic HPV types. Of the 252 women and girls who met the eligibility criteria, 45% were infected with at least one oncogenic HPV type and one‐third of participants had a persistent oncogenic infection. HPV16, 45, and 52 were the most frequently persistent types. Seventeen percent of women had persistent infections with oncogenic HPV types not within currently available vaccines (HPV35/39/51/56/59/68/82). Lower CD4 count significantly predicted HPV persistence ( P =0.024). Cervical cytology results were normal for 82.9% of participants, atypical squamous cells of undetermined significance for 2.4%, low‐grade squamous intraepithelial lesions for 11.5%, and high‐grade squamous intraepithelial lesions for 2.8%. Conclusion: Unvaccinated WLWH were infected with a wide range of oncogenic HPV types. The findings highlighted the importance of optimal treatment of HIV and continued cervical cancer screening as key steps toward the global elimination of cervical cancer. Abstract : Among 252 women living with HIV in Canada, 17.1% had persistent infection with non‐vaccine oncogenic human papillomavirus. Lower CD4 count predicted persistence.